Narrative change in psychotherapy - Ferreira, Tiago Bento da Silva (2015)
This thesis focuses on the processes of narrative change in psychotherapy. Previous reviews of the processes of narrative change in psychotherapy concluded that a general theory that details narrative concepts appropriate to understand psychotherapy processes, explains the dynamic processes between narratives, and how they relate to positive outcomes is needed. This thesis addresses this issue by suggesting a multi-layered model that accounts for transformations in different layers of narrative organization. Accordingly, a model was specified that considers three layers of narrative organization: a micro-layer of narrative innovations that disrupt the clients’ usual way of construct meaning from life situations (innovative moments), a meso-layer of narrative scripts that integrate these narrative innovations in narrative scripts that consolidate its transformative potential (protonarratives), and, finally, a macro-layer of clients’ life story (self-narrative). Globally, the empirical studies provided support for the conceptual plausibility of this model and to the specific hypothesis that were formulated on its basis. Our observations complement previous research that had underlined the integrative processes either by emphasizing thematic coherence or integration, by emphasizing the role of dynamicity and differentiation of narrative contents and processes. Additionally, they also contribute to expand previous accounts of narrative innovation through insights on the processes that characterize narrative innovation development across psychotherapy. These studies also emphasize the role of quantitative procedures in the study of narrative processes of change as they allow us to accommodate the complexity and dynamic properties of narrative processes.